LINKING COMPLEXITY LEADERSHIP FUNCTIONS TO ENTREPRENEURIAL ORIENTATION: EVIDENCE FROM TELECOMMUNICATION SECTOR - Khan, Chaudhary Bilal Ahmad; Ahmed, Riaz; Anantatmula, Vittal S. (APPS Publications, 2021)
Entrepreneurial orientation has not been much studied in conjunction with leadership to assess the organizational dynamics. This study aims to identify the interaction between complexity leadership functions and investigating their relationship with entrepreneurial orientation—this research study used survey questionnaire methods to collect cross-sectional quantitative data. To test research hypotheses, a sample of 288 respondents was collected from the telecommunication sector of Pakistan. Analysis extracted 15 fine-grain interactions for all the five complexity leadership functions. Findings indicate a significant relationship between generative leadership, information gathering leadership, information using leadership and entrepreneurial orientation, the partial relationship between administrative leadership and entrepreneurial orientation. However, an insignificant relationship was found between community-building leadership and entrepreneurial orientation because the Telecommunication sector might not focus much on community building compared to other practices of complexity leadership functions. Thus, this study makes a significant contribution to the body of knowledge in the domain of leadership and entrepreneurial leadership. For practitioners, the study highlights fine-grain interactions of complexity leadership functions to further augment entrepreneurial orientation.